Tourists' Local Food Experience: Linking Cultural Value, Knowledge, and Product Quality to Consumption Emotion and Satisfaction - Andih, Deisy Christina; Prawira, Mega Fitriani Adiwarna; Karnawati, Hennidah (Journal of Tourism Sustainability, 2025)
Local food consumption in tourism represents a cognitive and affective process through which visitors interpret cultural meaning and evaluate quality. This study develops and tests an integrative model linking cultural value, knowledge appreciation, and product quality to branding, perceived economic value, and consumption satisfaction. Data from 319 domestic and international tourists who experienced Indonesian gastronomy were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results show that cultural value and local identity strongly enhance knowledge and cultural appreciation, which in turn increase perceived product quality and support for local communities. These cognitive–ethical factors exert the greatest influence on emotional satisfaction, while branding alone shows no significant direct effect. Perceived quality and community alignment, rather than aesthetic branding, drive tourists' emotional engagement and satisfaction. Theoretically, this study introduces the concept of cognitive–ethical authenticity to explain how knowledge and moral resonance jointly produce satisfaction in gastronomic tourism. Managerially, the findings highlight that effective destination strategies should prioritise interpretive learning, transparent sourcing, and community-based experience design over symbolic branding. Overall, the research clarifies the cultural–cognitive pathway that underpins satisfaction in gastronomic experiences and advances a framework for authenticity-centred tourism development.